1996
DOI: 10.1002/(sici)1097-0215(19960822)69:4<278::aid-ijc7>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

The detection of disseminated tumor cells in bone marrow from colorectal-cancer patients by a cytokeratin-20-specific nested reverse-transcriptase-polymerase-chain reaction is related to the stage of disease

Abstract: The dissemination of cancer cells is a prerequisite in the development of micrometastases and solid metastases. Our previous examinations of these cells were based on immunocytological staining of tumor-associated antigens and cytokeratins. We have now developed a highly sensitive and specific detection method based on a nested reverse-transcriptasepolymerase-chain reaction (RT-PCR) of The main problem after surgical treatment of patients with colorectal, gastric or pancreatic cancer is the frequent recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
1
4

Year Published

1998
1998
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(71 citation statements)
references
References 16 publications
0
66
1
4
Order By: Relevance
“…CK20 RT-PCR assays were performed as published (Soeth et al, 1996). Each sample was investigated twice and scored positive, if at least in one assay a specific amplification occurred.…”
Section: Rt-pcr Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…CK20 RT-PCR assays were performed as published (Soeth et al, 1996). Each sample was investigated twice and scored positive, if at least in one assay a specific amplification occurred.…”
Section: Rt-pcr Assaymentioning
confidence: 99%
“…In a number of clinical CK20 RT-PCR studies, comparable diagnostic specificities have been achieved for conventional (Burchill et al, 1995), nested RT-PCR (Soeth et al, 1996) and even double-nested RT-PCR (Funaki et al, 1998) systems. Recent studies have assigned clinical significance and prognostic value to the detection of CK20 mRNA-positive cells in bone marrow and peripheral blood samples of breast, gastric, pancreatic and colorectal cancer patients (Soeth et al, 1996(Soeth et al, , 1997Bostick et al, 1998;Weitz et al, 1998).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In the 1950's, cytological studies demonstrated that circulating cancer cells from solid tumors are detectable in the blood of cancer patients (Engell, 1955). In the 80's and 90's highly sophisticated techniques were developed, such as immunocytology (Redding et al, 1983;Schlimok et al, 1987;Juhl et al, 1994) and RT -PCR (Gerhard et al, 1994;Burchill et al, 1995;Soeth et al, 1996) enabling detection of circulating colon cancer cells in various body compartments. In colon cancer finding of minimal residual disease in bone marrow, peritoneal lavage and lymph node samples correlated with poor survival (Lindemann et al, 1992;Schott et al, 1998;Liefers et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have reported use of the RT-PCR method to detect prostatic cancer cells (Fadlon et al, 1996;Henke et al, 1997;Melchior et al, 1997), melanoma cell (Foss et al, 1995), and neuroblastoma cells (Burchill et al, 1995b) in peripheral blood by amplifying prostatic specific antigen, tyrosinase and tyrosine hydroxylase respectively. Some investigators used the epithelium-specific cytokeratin (CK8, CK19 or CK20) as a marker for detecting epithelial cancer cells which did not have any specific markers (Burchill et al, 1995a;Krismann et al, 1995;Soeth et al, 1996). However, Burchill et al (1995a) and Krisman et al (1995) reported that CK8 and CK19 were amplified in a high proportion of normal peripheral blood samples, but CK20 was not amplified in any normal blood samples.…”
Section: Discussionmentioning
confidence: 99%